2019
DOI: 10.1002/jcd.21660
|View full text |Cite
|
Sign up to set email alerts
|

The maximum, supremum, and spectrum for critical set sizes in (0,1)‐matrices

Abstract: If D is a partially filled-in (0,1)-matrix with a unique completion to a (0,1)-matrix M (with prescribed row and column sums), then we say that D is a defining set for M. A critical set is a minimal defining set (the deletion of any entry results in more than one completion). We give a new equivalent definition of critical sets in (0,1)matrices and apply this theory to Λ m m 2 , the set of (0,1)matrices of dimensions m m 2 × 2 with uniform row and column sum m. The smallest possible size for a defining set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The optimum values for the mass ratio ϕ cannot be obtained using Eqs (8) and (10). To overcome this problem, we use the Taylor series of those equations with respect to the parameter ϕ of order n as follows (see references [24,30]), https://doi.org/10.1371/journal.pone.0228955.g008…”
Section: Pressure Control By Reining Mass Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum values for the mass ratio ϕ cannot be obtained using Eqs (8) and (10). To overcome this problem, we use the Taylor series of those equations with respect to the parameter ϕ of order n as follows (see references [24,30]), https://doi.org/10.1371/journal.pone.0228955.g008…”
Section: Pressure Control By Reining Mass Ratiomentioning
confidence: 99%
“…In statistics, a confidence interval (CI) is a type of interval estimate, computed from the statistics of the observed data, that might contain the true value of an unknown parameter [28][29][30]. Therefore, the confidence interval for the optimum values of the pressure P is defined as ½min P 0 ; � P optimal ; max P 0 ; � P optimal Þ, where min P 0 ; � P optimal and max P 0 ; � P optimal are given by,…”
mentioning
confidence: 99%
“…Cavenagh and Wright [4] studied critical sets, that is, defining sets which are minimal in the sense that the removal of any element destroys the property of being a defining set. They showed that the complement of a critical set is itself a defining set.…”
Section: Introductionmentioning
confidence: 99%